2006
DOI: 10.1126/science.1118221
|View full text |Cite
|
Sign up to set email alerts
|

Comment on "Iron Isotope Constraints on the Archean and Paleoproterozoic Ocean Redox State"

Abstract: Rouxel et al . (Reports, 18 February 2005, p. 1088) argued that changes in the iron isotopic composition of sedimentary sulfides reflect changes in the oxidation state of the atmosphere-ocean system between 2.3 and 1.8 million years ago. We show that misinterpretations of the origins of these minerals undermine their conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In this context, partial oxidation associated with BIF precipitation would have left a residue of isotopically light Fe(II) aq (<À0.15‰/amu). Yamaguchi and Ohmoto (2006) and Archer and Vance (2006) questioned this interpretation and suggested instead that the light Fe isotopic compositions measured in >2.3 Ga pyrite grains reflect microbial cycling of Fe in the sediment by dissimilatory iron reduction (however, see Rouxel et al, 2006). Studies of shallow sediment profiles (Severmann et al, 2006;Staubwasser et al, 2006) have shown that such redox cycling does occur in present-day sediments, producing Fe(II) aq in porewaters with F Fe as low as À1.5‰/amu.…”
Section: The Fe Isotopic Composition Of Eoarchean Seawatermentioning
confidence: 89%
“…In this context, partial oxidation associated with BIF precipitation would have left a residue of isotopically light Fe(II) aq (<À0.15‰/amu). Yamaguchi and Ohmoto (2006) and Archer and Vance (2006) questioned this interpretation and suggested instead that the light Fe isotopic compositions measured in >2.3 Ga pyrite grains reflect microbial cycling of Fe in the sediment by dissimilatory iron reduction (however, see Rouxel et al, 2006). Studies of shallow sediment profiles (Severmann et al, 2006;Staubwasser et al, 2006) have shown that such redox cycling does occur in present-day sediments, producing Fe(II) aq in porewaters with F Fe as low as À1.5‰/amu.…”
Section: The Fe Isotopic Composition Of Eoarchean Seawatermentioning
confidence: 89%
“…The present continental flux of Mo, like that of Re and Os, is largely derived from organic matter-rich sulfidic shales; at the time of the GOE, the pre-GOE organic matter-rich sulfidic shales were not significantly enriched in Mo above crustal levels (Holland 2004;Yamaguchi 2002;Scott et al 2008). The predominant crustal reservoir of Mo that oxidized to form molybdate at this time would have been crystalline crustal rocks with generally low Mo content.…”
Section: Molybdenum Concentrations In Euxinic Shalesmentioning
confidence: 97%
“…doi:10. 1016/j.gca.2008.04.035 Mars, and the mobility of a host of contaminants in modern earth settings (Straub et al, 2001;Benison and LaClair, 2003;Edwards et al, 2004;Emerson and Weiss, 2004;Kappler and Newman, 2004;Roden et al, 2004;Ferris, 2005;Kump and Seyfried, 2005;Rouxel et al, 2005;Rouxel et al, 2006;Yamaguchi and Ohmoto, 2006;Stucki et al, 2007;Neubauer et al, 2008). In any of these environments geochemical control on microbial ecology can be manifested in diverse ways, but one key factor is to consider the rates at which organisms can utilize existing substrates including electron donors and acceptors to garner energy for growth.…”
Section: Introductionmentioning
confidence: 99%